Effect of variable axial force on the vibration of a thin beam subjected to moving concentrated loads - Peter, O. Olatunji (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2023)
Link to publisher's homepage at https://amci.unimap.edu.my/